Experiencing Being Judged: Making Visible School Community Expectations of Rural Principals - Rinehart, Kerry Earl (Australian and International Journal of Rural Education, 2022)
Judgements of the work of school principals may be formal through an appraisal process or informal from students, teachers, parents, and members of the community in which the school operates. This article focuses on New Zealand rural primary school principals’ experiences of informal expectations—and judgements about whether they meet these expectations—from school community members. The aim of this study is to illustrate principals’ work in responding to community expectations and the contextual factors of school settings, and to advocate for more overt policy and process attention to such work in the formal appraisal of principals. Using Deweyan pragmatism for a theoretical approach, research evidence was generated from semi‑structured interviews with principals and ex‑principals of small rural schools. Abductive analysis was used. Not only do principals’ relationships with individuals and groups within their communities impact on their work and ability to succeed in their professional ambitions for school and students, but relationships between groups in the school community may also influence local judgements of that work. These relationships can be important aspects of schools’ historical contexts. The time principals spend prioritising and responding to community expectations is notable and should be reflected in policy and processes of principal appraisal. Insights from this research are likely to be useful for principals and their mentors, as well as for facilitators of preparation programs and inservice professional learning for principals and aspiring principals.